Dinochloa Scandens (Poaceae-Bambusoideae): Distribution, Habitat Preference, and Notes on Synonymy - I Putu Gede P. Damayanto; Syadwina H. Dalimunthe; Megawati Megawati (UIN Sunan Gunung Djati Bandung, 2021)
The distribution of Dinochloa scandens is unclear. World bamboo checklists suggest it is relatively widespread in Malesia. Here we clarify issues with herbarium specimen identification. Besides, a synonym name of D. scandens, namely D. macrocarpa collected from the Philippines, needs to be reviewed. The study aims to provide information on distribution and to review the synonym of D. scandens. The habitat preferences of D. scandens are also presented. We carried out targeted fieldwork at Gunung Halimun-Salak National Park in West Java in 2019 and extensive examination of herbarium specimens from Herbarium Bogoriense and online portals to accurately circumscribe this species. All data were analyzed descriptively. Distribution, altitude, and rainfall maps for D. scandens were produced with ArcGIS Pro. Our examination on the specimens suggests that D. scandens is indeed endemic to West Java and Banten Provinces in Indonesia. This bamboo species can be found in lowland to mountain forests with an altitude of 20-1400 m, in areas with annual rainfall between 3000-4000 mm. We support D. macrocarpa as an accepted name for a bamboo species from the Philippines and remove it from synonymy with D. scandens due to clear differences in the fruit compared to specimens of D. scandens across its range.